Disclosure Status and Associated Factors Among Children on Antiretroviral Therapy in Ethiopia - Tucho WA; Tekelehaimanot AN; Habte MB (Dove Medical Press, 2021)
Walelign Atomsa Tucho,1 Aderajew Nigusse Tekelehaimanot,2 Mahilet Berhanu Habte2 1Department of Disease Prevention and Control, Bench Sheko Zone Health Office, Mizan-Aman, Southwest Ethiopia; 2Department of Population and Family Health, Faculty of Public Health, Jimma University, Jimma, EthiopiaCorrespondence: Mahilet Berhanu Habte Tel +251-912246413Email mahitesfa.mt@gmail.comBackground: The World Health Organization recommends that children should be informed of their HIV status at age 6- 12 years. However, disclosure of HIV status among children is very low in resource-limited areas, particularly in Ethiopia. So, the aim of this study was to determine the prevalence of disclosure and associated factors among a cohort of HIV-infected children in southwest Ethiopia.Methods: A facility-based cross-sectional study design was employed among caregivers of HIV-positive children aged 6- 15 in Bench sheko and West Omo zone Southwest Ethiopia, from March 1 to April 20, 2020. Study participants were included using a consecutive sampling technique. Data were collected using a pretested interviewer administered questionnaire and checklist. A multivariable logistic regressions model was used to identify independent predictors of disclosure. The significance of association was declared by AOR at 95% confidence and a p-value < 0.05.Results: A total of 327 participants were involved in the study yielding a 95% response rate. The prevalence of HIV-positive status disclosure was 45.6% (95% CI=41.01- 51.02). Caregiver secondary education and above (AOR=3.16, 95% CI=1.07- 9.34), caregiver discussed about disclosure with health professionals (AOR= 9.56, 95% CI=4.88- 18.74), child age 10- 15 year old (AOR=3.64, 95% CI=1.64- 8.08), duration on ART > 5 years (AOR=5.08, 95% CI=1.57- 16.37), treatment follow-up at hospital (AOR=2.23, 95% CI=1.27- 5.01) and having treatment support for Children (AOR=3.84, 95% CI=1.88- 7.85) were independent predictors of HIV-positive status disclosure.Conclusion: Disclosure of HIV status to children is low. Caregivers educational status, caregivers discussion with health professional, older child, duration on ART of more than 5 year, getting treatment service from hospital, and having a treatment support group are factors that enable disclosure. Therefore, concerted efforts based on the findings of this study will be required to improve the disclosure status among HIV-positive children.Keywords: disclosure, antiretroviral therapy, child